1993
DOI: 10.1021/ma00064a001
|View full text |Cite
|
Sign up to set email alerts
|

Novel photocrosslinkable liquid-crystalline polymers: poly[bis(benzylidene)] esters

Abstract: A new class of photo-cross-linkable main-chain liquid crystalline polymers (PMCLCPs) containing bis(benzylidene)cycloalkanone groups have been synthesized and studied for their liquid crystalline and photochemical properties. The bis(benzylidene)cycloalkanone group in the chain functions both as a mesogen and as a photoreactive center. All of the polymers exhibit a nematic mesophase. Two kinds of photoreactions, namely, photoisomerization and photo-cross-linking, operate in these polymers. Above T" at the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 19 publications
2
50
0
Order By: Relevance
“…This corresponds to formation of cyclobutane ring due to cycloaddition reaction in both polymers. 56 This behavior is also confirmed by studying the change in inherent viscosity at 30 8C (in DMSO) by using Ubbelohde viscometer at a concentration of 0.5 g/dL under UV exposure [ Fig. 4].…”
Section: Photo Responsive Propertiesmentioning
confidence: 66%
See 1 more Smart Citation
“…This corresponds to formation of cyclobutane ring due to cycloaddition reaction in both polymers. 56 This behavior is also confirmed by studying the change in inherent viscosity at 30 8C (in DMSO) by using Ubbelohde viscometer at a concentration of 0.5 g/dL under UV exposure [ Fig. 4].…”
Section: Photo Responsive Propertiesmentioning
confidence: 66%
“…These results support the spectral studies, which are discussed in previous reports on similar class of polymers. 25,26,56 CONCLUSIONS Novel epoxy terminated photoactive linear and hyperbranched liquid crystalline benzylidene polyesters with pendant hydroxyl groups were synthesized by polyad- 1 H NMR spectrum of LECPE in DMSO-d 6 during photolysis (0-120 min). dition reaction of photoactive epoxidised bisbenzylidene cyclopentanone monomer with terephthalic acid and trimesic acid respectively.…”
Section: Photo Responsive Propertiesmentioning
confidence: 99%
“…[19] Borden et al [20,21] synthesized photo-responsive linear bis(benzylidene) polycarbonates and observed that they were poorly soluble. In 1993, Gangadhara and Kishore [6] prepared polybis (benzylidene) esters from tetragolic acid dichloride and bis(4-hydroxy benzylidene) cyclohexanone and reported improved solubility. The present investigation showed appreciable solubility in polar solvents.…”
Section: Solubility Of Copolyesteramidesmentioning
confidence: 99%
“…[1][2][3][4][5] Photocrosslinkable polymers have attracted considerable attention in the research field because of their interesting mechanical, electrical and optical properties. Photocrosslinkable polymers find potential applications in the preparation of photo curable coating, photocrosslinked hydrogels, optical lithographic materials, photo sensitizers, photo resists, photorefractive materials [6 ] and information storage devices. Polymers having photodimerizable groups find applications in immobilization of enzymes [7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Synthesis of bisbenzylidene cycloalkanone molecule was first reported by Samdahl [1,2]. This photo-active molecule has attracted the attention of macromolecular chemists [3][4][5][6][7]. They were found to be a potential mesogen [8][9][10] and their incorporation in the polymeric backbone has imparted thermotrophic liquid crystalline property to the polymeric materials.…”
Section: Introductionmentioning
confidence: 99%